GASTRODUODENITIS IN CHILDREN: CURRENT STATE OF THE PROBLEM (International Journal of Scientific Pediatrics, 2025)
The review is devoted to the current state of the problem of gastroduodenitis in children. Current data on the prevalence and age-specific clinical picture of the disease are presented. The leading etiological factors are considered, among which Helicobacter pylori plays a key role, as well as dietary errors, stress influences and genetic predisposition. The evolution of classifications is described taking into account morphological, etiological and clinical-functional features, the importance of the SDDS concept for scientific purposes is emphasized. Modern diagnostic algorithms are described, including endoscopy with multiple targeted biopsy, non-invasive ^13C-urease and faecal antigen tests, "gastropanel" and promising inflammation markers. The article provides an overview of current eradication and antisecretory therapy regimens (proton pump inhibitors, potassium blockers, bismuth-containing quadruple and sequential regimens), the role of gastroprotectors, probiotics and diet therapy. The principles of prevention and rehabilitation, including lifestyle and psychoemotional status correction, are covered. Unresolved issues are highlighted: the growth of antibiotic resistance of H. pylori, the safety of long-term use of PPIs, the lack of validated non-invasive biomarkers and pediatric disease activity scales. The need for multicenter studies and the development of AI algorithms to objectify endoscopic assessment is noted.
Keywords: gastroduodenitis; children; Helicobacter pylori; endoscopy; proton pump inhibitors; quadruple therapy; probiotics; diagnosis; prevention